You are on page 1of 3

# 5

2

12. I =∫ sen x cos xdx
4

2

2

(

)

1−sec x
I=
dx
2

2

I =∫ sen x ∙ senx ∙ cos xdx
2

( se n2 x ) =( 1−cos2 x )
4

I =∫

2

2

4

sen x=1−2 cos + cos

I =∫ ( 1−2 cos 2 x +cos 4 x ) senx∙ co s2 xdx

senx ∙ cos 4 xdx +¿ ∫ senx∙ cos6 xdx
I =∫ senx ∙ cos2 xdx−2∫ ¿

1−sec 2 x+ sec 2 x
dx
4

1
sec 2 xdx
4∫
1
1
I = ∫ dx− ∫ ¿
4
2

sec 2 +¿

1
1
1
I = x− tgx+ tgx+c
4
2
4
6

u=cosx
du=−senxdx
4

3

28. I =∫ tan x ∙ se c xdx

6

u du−¿ ∫ u du

3

2

3

I =∫ tan x ∙ tan x ∙ sec xdx
2

2

I =∫ u2 du+2∫ ¿

1

( ta n 2 x ) =( 1−sec 2 x )
I=

−cos 3 x
cos5 x cos 7
+2
+
+c
3
5
7

18. I =∫ sen 2 x ∙ cos 4 xdx

I =∫

1
sen 6 x + sen−2 x
2∫

I=

1
sen 6−sen 2 x
2∫

sen 6 x −¿∫ sen 2 x
1
I = ∫¿
2
I=

2

−1
∙ cos 6 x +cos 2 x+ c
2

3

2

3

3

5

tan x ∙ sec xdx−¿ ∫ ta n x ∙ sec xdx
I =∫ ¿
u=secx
du=secx ∙ tanx
3

5

u du−¿∫ u du
I =∫ ¿
I=

u 4 u6
− +c
4 6

I=

sec 4 x sec 6 x

+c
4
6

4

2

2

I =∫ ( 1−sec 2 x ) tan 3 x ∙ sec 3 xdx

24. I =∫ tan xdx

tan x ¿ dx
¿
I =∫ ¿

1

tan x=1−sec x

1
[ sen ( 2+ 4 ) x+sen ( 2−4 ) x ]
2

I=

3

I =∫ ta n x ∙ tanx ∙ta n x ∙ sec xdx

4

30.

tan x
dx
∫ sec
5
x

∫ dx √ 9−x 2 x=3 senθ dx=3 cosθdθ I =∫ 3.2 2 dx=sec θdθ 2 dx= I= sec θdθ 2 1 sec2 θdθ ∫ 2 √ tan 2 θ+1 1 se c 2 θ I= ∫ dθ 2 √ sec 2 θ I =∫ I= 2 sec θ dθ secθ 1 secθdθ 2∫ 1 I = ln |secθ+tanθ|+c 2 √ 4 x 2 +1 2x 1 1 I = ln |√ 4 x 2 +1+2 x|+ c 2 6.3 cosθ I= 1 1 dθ ∫ 9 sen 2 θ I= 1 csc 2 θdθ ∫ 9 . ∫ dx √ 4 x 2+ 1 I =∫ dx √(2 x )2+(1)2 2 x =tanθ 3 cosθdθ 3 sen θ √ 9−9 sen 2 θ 2 2 I= 1 cosθdθ 3 ∫ sen2 θ .

1 I = ctanθ +c 9 3 x √ 32−x 2 I= 1 √ 9−x 2 +c 9 x I= −√ 9−x2 +c 9x .